Réponses

Meilleure réponse !
2014-10-02T18:51:41+02:00
EXERCICE 2 
f(x) = √2 x -2 

1/ f(-√2) = √2 × (-√2) -2 
             = -√2²-2 
             = -2 -2 
             = -4 : l'image de -√2 est -4 

2/ f(x) = √2 x -2 = 0
           √2 x = 2 
           x = 2 / √2  = 2 √2 /√2²  = 2 √2 / 2 = √2  l'antécédent de 0 est √2 

    f(x) = √2 x -2 = √2
            √2 x = √2 +2 
            x = √2 / √2 + 2 / √2 = 1 + √2  l’antécédent de √2 est 1 + √2 

3/ placer les points (√2;0) (-√2;4) (1+√2;√2)

4) f(x) > x - 1 
    √2 x -2 > x - 1
    √2 x - x > -1 + 2 
    x (-1 + √2) > 1 
    x > 1/ (-1 + √2)